Pengaruh Budaya Organisasi dan Pelatihan Kerja Terhadap Produktivitas Kerja Karyawan Alih Daya Pada PT Pronata Data Insani - Lidya Fathnin (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
Employee work productivity is one of the important factors in supporting the achievement of company goals. Organizational culture and job training are aspects that play a role in improving employee capabilities and work effectiveness. This study aims to analyze the influence of organizational culture and job training on the work productivity of outsourced employees at PT Pronata Data Insani. The method used in this study is a quantitative approach with a causal associative research type. The population and sample of the study amounted to 42 employees who were determined using a saturated sampling technique. Data collection techniques were carried out through questionnaires, observations, interviews, and documentation. Data analysis used multiple linear regression with the help of IBM SPSS Statistics version 29. The results of the study showed that organizational culture partially had no significant effect on work productivity with a significance value of 0.172. Conversely, job training had a positive and significant effect on work productivity with a significance value of 0.007. Simultaneously, organizational culture and job training had a significant effect on work productivity with a significance value of 0.001 and were able to explain work productivity by 35.9%.